Cointegration analysis of US M2 and gold price over the last half century - Richard Synek (European Financial and Accounting Journal, 2024)
In this article I have analysed the long-term relationship between US M2 money supply and the price of gold per troy ounce using Engle-Granger cointegration. The analysis shows the existence of long-term price dependency of gold in relation to US M2 money supply. M2 was used in two variants, seasonally adjusted and not seasonally adjusted. No relevant difference was observed between them. A period spanning 53 years, from 1970 to 2023, was analysed. An EC model using monthly observations indicates very weak correlation between the change of M2 and the subsequent change of the gold price, so semiannual observations were used instead which proved fully conclusive. This, together with results from the long-term model, confirms long price cycles and fluctuation around its equilibrium price lasting for years, which allows the use of gold as a hedge against increasing M2. This article may prove beneficial in filling the gap as it confirms gold price to be dependent on US M2 on longer time span analysed than previous studies and is fully able to explain gold price analysing dependency of two variables only.
Keywords: C58; E31; E44; E51; G12; 650; Cointegration Analysis; Gold; M2; Money Supply